'It is Really Important That We Sometimes Remember the Children and Their Views Rather than Just Our Own': The Presentation and Representation of Children's Views in the Child Protection Conference. Issue 4 (8th August 2022) - Ogle, Justine; Vincent, Sharon
Abstract : In the UK, children are entitled to have their views, wishes and feelings conveyed to a child protection conference in person or through professional representation. This paper presents findings from a qualitative study undertaken in a local authority in England which explored perspectives of attending a conference in person and investigated how children's views were represented when they were absent. Findings emerged through interviews with four children, focus groups conducted with four social workers and four conference Chairs, and case record analysis of reports submitted to and generated in child protection conferences for twenty-eight children. Three interrelating discourses of childism, participation and autonomous professional practice emerged within an overarching conceptualisation of power and generational ordering. The findings support contemporary understandings of the privileging of protection rights over participatory rights within child protection practices and add to the limited international evidence base concerning the extent to which young children can express their views, wishes and feelings. They also suggest a need to evaluate the impact of strengths-based practice frameworks, and approaches for assessment and recording practices that promote authentic participation for children across all age ranges.